(untitled) (Revista Contexto & Saúde, 2025)
Introduction: During the pandemic, health services were restructured to meet the demand from COVID-19 cases, which led to the neglect of other diseases, including tuberculosis (TB). Objective: Assess whether there was a change in the number of TB cases identified using the rapid molecular test for tuberculosis and whether there was an increase in resistance to antituberculosis drugs after the pandemic, both in the general population and the prison population. Methodology: Individuals who underwent molecular rapid testing for tuberculosis (MRT-TB) and sensitivity tests to anti-TB drugs were evaluated at the Northern District Municipal Laboratory, during the period from January 2018 to December 2022. Results: We included 12,208 (81.7%) individuals from the general population and 2,731 (18.3%) from the prison population (PP) of the city of Manaus. The initial year of the pandemic, 2020, had the highest percentage of positive tests (20.6%, n=205) in the general population. This trend continued in the following years, being equal to 12.5% (n=347) and 12.9% (n=392), in 2021 and 2022, respectively. However, in the PP, the years with the highest rates of positive exams were 2018 and 2019, with 13.1% (n=55) and 20.5% (n=50) respectively, with a significant reduction in the percentage of positive exams in later years. Resistance to the drug Isoniazid was the most frequent resistance found in both the general population and the prison population, but without a significant increase. Conclusion: The COVID-19 pandemic negatively influenced the control of tuberculosis, increasing the number of cases of this disease in the general population, and it is necessary to improve health policies to control and reduce cases of this disease.